EVALUATION OF THE FREE RADICAL SCAVENGING OF TECTOQUINONE COMPOUND ISOLATED FROM SYZYGIUM OBLANCEOLATUM (C.B.ROB.) MERR - Najib, Ahmad; Handayani, Virsa; Jaelani, Muhammad Rizki (Universal Journal of Pharmaceutical Research, 2023)
Aim and objective: In this study, the free radical scavenging of tectoquinone compound isolated from leaf of Syzygium oblanceolatum (C.B. Rob.) Merr was investigated by assessing their capacity to scavenge free radicals using the DPPH (2, 2-diphenyl-1-picrylhydrazyl) assay. Methods: The quantitative assessment of antioxidant activity was conducted using a UV-Vis spectrophotometric approach, with measurements taken at a wavelength of 516 nm. Results: The IC50 value, representing the concentration required to inhibit 50% of the DPPH radicals, was determined to be 66.362 μg/mL, indicating a moderate free radical-scavenging activity. Conclusion: These findings suggest that tectoquinone compounds possess a discernible ability to against free radical, though further research may be necessary to optimize their potential applications in health and medicine. Peer Review History: Received: 1 August 2023; Revised: 10 September; Accepted: 27 October; Available online: 15 November 2023 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewers: Dr. Bilge Ahsen KARA, Ankara Gazi Mustafa Kemal Hospital, Turkey, ahsndkyc@gmail.com Dr. Sangeetha Arullappan, Universiti Tunku Abdul Rahman, Malaysia, sangeetha@utar.edu.my